تجليات الرؤيا في شعر محمد عمران - حسن, محمد معلا; جابر, يوسف حامد; علي, محمد إبراهيم (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
يحاول هذا البحث رصد أهم تجليات الرؤيا في شعر محمد عمران, منطلقاً من تأصيل مصطلح ( الرؤيا ) , واكتناه العلاقة بينه وبين مصطلح ( الرؤية )؛ إذ تقوم الرؤية على المشاهدة المادية و الواقعية والحسية للأشياء, أما دور الرؤيا فيكمن في كيفية إبراز هذه المشاهدة وصوغها بالاعتماد على سعة خيال الشاعر وقدرته الفنية من جهة, وما تخلفه هذه المشاهدة من انفعالات داخلية عنده من جهة أخرى . وقد تجلت الرؤيا في شعر محمد عمران في (الحلم الشعري) وعلاقاته المتشعبة مع الواقع واللاشعور والخيال, كما تجلت في ( النبوءة الشعرية ) بوصفها تجاوزاً زمانياً ومكانياً للواقع المعيش واستشرافاً قائماً على الحدس؛ ليخلص البحث إلى خاتمة تُبيّنُ دور الرؤيا في رفد التجربة الشعرية لمحمد عمران بمعطيات حداثية على مستوى المضمون . This research aims to examine the most crucial manifestations of vision dream in Muhammad Omran's poetry. This work begins with digging deep into the essence of the term ( vision dream ) and exploring the significant development from the lexical meaning to the term meaning , to end up with an insight of the relation between ( vision dream ) and ( vision ) . While vision is the physical, true and sense viewing of things , the role of vision dream lies in finding the means to highlight this view and formulate it depending on the poet's imagination and artistic abilities on the one hand, and the internal emotions this view stimulates on the part of the poet on the other hand . Vision dream was manifested in Omran's poetry throughout (The Poetic Dream), and its multi-dimensional relation with reality, subconsciousness and imagination. It was manifested too throughout (The Poetic Prophecy) being an override in time and place of our daily life and an exploration through future intuition. The research concludes in examining the role of vision dream in supplementing Muhammad Omran's poetry with a modern content.